2015
DOI: 10.3928/02793695-20150923-03
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Disordered Gambling Among Older Adults

Abstract: The current study is a secondary analysis that describes the mental, social, and economic health impacts of disordered gambling in older adults recovering from pathological gambling. The study sought to answer the following research questions: (a) What are the problem behaviors in the mental, social, and economic health dimensions?; and (b) What is the association between mental, social, and economic health impact dimensions and the South Oaks Gambling Screen score? The study population comprised a convenience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Many older adults are transitioning out of the labour force or retired and therefore have limited resources to recover from financial losses (Grant Stitt, Giacopassi, & Nicols, 2003; Ladd, Molina, Kerins, & Petry, 2003; McCready et al, 2005; Petry, 2002). Older adults also have more time for leisure activities such as gambling and are also more likely to experience feelings of uselessness, boredom, and income inadequacy, which may motivate them to gamble (Kerber, Adelman-Mullally, Kim, & Schafer Astroth, 2015; Kim & Moen, 2002; Loroz, 2004; McNeilly & Burke, 2000; Parekh & Morano, 2009; Wiebe, 2002).…”
mentioning
confidence: 99%
“…Many older adults are transitioning out of the labour force or retired and therefore have limited resources to recover from financial losses (Grant Stitt, Giacopassi, & Nicols, 2003; Ladd, Molina, Kerins, & Petry, 2003; McCready et al, 2005; Petry, 2002). Older adults also have more time for leisure activities such as gambling and are also more likely to experience feelings of uselessness, boredom, and income inadequacy, which may motivate them to gamble (Kerber, Adelman-Mullally, Kim, & Schafer Astroth, 2015; Kim & Moen, 2002; Loroz, 2004; McNeilly & Burke, 2000; Parekh & Morano, 2009; Wiebe, 2002).…”
mentioning
confidence: 99%
“…The increase in casinos across the country resulted in entertainment rivalry as casinos entertainment started to attract adults. Hence, gambling revenues especially casino-gambling revenues surpassed theme parks and movie theatres and moved casino gambling into the mainstream of American entertainment (Conway, 2015;Kerber et al, 2015;Martin et al, 2011;Stansbury et al, 2015;Thompson and McNeilly, 2016;Tse et al, 2012). Despite this growth, casino-gambling tax revenues are not the same across all states.…”
Section: Results From the Literaturementioning
confidence: 99%
“…Overall, gambling-related problems that lead to problem gambling or gambling disorder are undisguised, undetected, and uncovered until the difficulties have exacerbated. Adult gamblers who face gambling-related problems suffer lack of detection, or, they conceal such problems due to embarrassment, shame, guilt, and lack knowledge of where to seek help (Baxter et al, 2016;Kerber et al, 2015;Martin et al, 2011, Stansbury et al, 2015. Gambling-related problems could also result in increased social services intervention, prevention, and treatment (Gattis and Cunningham-Williams, 2011;Stansbury et al, 2015;Walker and Sobel, 2016).…”
Section: Results From the Literaturementioning
confidence: 99%
“…Family support, for example, is very important: a recent study showed that, among older gamblers, family support was essential in helping to implement control strategies for responsible gambling (40). To help identify GD in vulnerable older people, Kerber et al proposed the acronym “CASINO” to help everyone to remember the impact and factors linked to disordered gambling in older adults: Chronic health problems, Affective disorders, Serious risk of suicide, Incarceration, NO money, credit card debts, and financial problems (57). This acronym includes individual and social determinants.…”
Section: Discussionmentioning
confidence: 99%